2016
DOI: 10.7150/jca.14745
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Ubiquitin-conjugating Enzyme UBE2D3 Promotes Telomere Maintenance and Radioresistance of Eca-109 Human Esophageal Carcinoma Cells

et al.

Abstract: Ubiquitin-conjugating enzyme UBE2D3 is an important member of the ubiquitin-proteasome pathways. Our previous study showed that the expression of UBE2D3 was negatively related to human telomerase reverse transcriptase (hTERT) and radioresistance in human breast cancer cells. However, in esophageal carcinoma, the exact effects and mechanisms of UBE2D3 in radioresistance remain unclear. This study shows that UBE2D3 knockdown was associated with significant increases in radioresistance to X-rays, telomerase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…While UBE2D3 has been described to be an in vitro tumor suppressor for its role in modulating radiosensitivity [71, 72] and proliferation [73], the in vivo data of TCGA suggested that higher UBE2D3 expression predicts poorer clinical outcomes. One study has shown that the targeting of RMND5A significantly attenuates HeLa cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…While UBE2D3 has been described to be an in vitro tumor suppressor for its role in modulating radiosensitivity [71, 72] and proliferation [73], the in vivo data of TCGA suggested that higher UBE2D3 expression predicts poorer clinical outcomes. One study has shown that the targeting of RMND5A significantly attenuates HeLa cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Ube2d3 is an important member of the ubiquitin‐proteasome pathways that has attracted increasing attention from biologists due to its role as the initial ubiquitinating enzyme of key regulatory molecule of p53 . Ube2d3 affects cancer progression, cell apoptosis, and DNA damage repair, for example, Ube2d3 knockdown‐induced apoptosis . In this study, the RNA‐seq and qRT‐PCR results show that the expression of Ube2d3 in Exp‐ERRγ cells was significantly reduced compared with the control group.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, the RNA‐seq and qRT‐PCR results show that the expression of TFPT in Exp‐ERRγ cells was significantly increased compared with the control group. Ube2d3 is an important member of the ubiquitin‐proteasome pathways that has attracted increasing attention from biologists due to its role as the initial ubiquitinating enzyme of key regulatory molecule of p53 . Ube2d3 affects cancer progression, cell apoptosis, and DNA damage repair, for example, Ube2d3 knockdown‐induced apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Cluster 8, which has the highest genomic instability, is enriched for a gain on 7q (including SMURF1; also increased in expression) and a loss on 4q, and high expression of 35 genes including PIK3CA and the transcriptional regulator YEATS2, as well as low expression of the ubiquitin-conjugating enzyme UBE2D3, a phenotype linked to cell cycle progression, reduced apoptosis, and telomere stability 28 . In addition, these tumors show reduced expression of genes for protein secretion, unfolded protein response, and RNA degradation.…”
Section: Liver Hepatocellular Carcinoma Hepatocellular Carcinoma Ismentioning
confidence: 99%